Computer-simulated mirror osteotomy in the treatment of post-traumatic cubitus varus deformity in children - WenQiang Xu; YongFei Fan; XiuLin Ma; JianQiang Zhang; WenZhi Bi; ChaoYu Liu; Wei Wang (BMC Musculoskeletal Disorders)
Abstract Purpose To explore the feasibility and early clinical efficacy of computer-based mirroring technology in simulating osteotomy for the treatment of post-traumatic cubitus varus deformity in children. Methods A retrospective analysis was conducted on the data of 26 patients with cubitus varus deformity who were admitted between June 2019 and June 2024. Among them, there were 19 males and 7 females, with an average age of 8.12 ± 2.83 years (ranging from 5 to 15 years). The time from injury to surgery ranged from 13 to 84 months, averaging at 27.85 ± 21.91 months. The carrying angle and anteversion measured on full-length anteroposterior radiographs of both upper extremities and lateral radiographs of the elbow joint were used as osteotomy parameters. Low-dose CT scans of both upper extremities of the pediatric patients were performed to reconstruct three-dimensional (3D) models of the affected limb for computer-simulated osteotomy. The 3D mirror-imaging technique of the unaffected side was applied for overlay comparison, and the osteotomy parameters were adjusted accordingly. Surgeries were performed based on the final parameters obtained. Intraoperative data such as surgical duration and blood loss were recorded, and regular postoperative follow-ups were conducted with X-ray examinations to observe bone callus formation in the osteotomy area. At the final follow-up, the carrying angle, anteversion, and range of motion (flexion and extension) of the elbow joints on both the affected and unaffected sides were measured, and elbow function was assessed using the Mayo score. Results The surgical duration for the 26 patients ranged from 35 to 55 min, averaging at 44.23 ± 7.83 min, with an average blood loss of 32.12 ± 6.35 ml (ranging from 20 to 40 ml). The mean follow-up duration was 31.12 ± 15.81 months (ranging from 6 to 60 months). Kirschner wires (K-wires) were removed 8–12 weeks postoperatively, and plates were taken out 4–6 months later. During the follow-up period, two patients experienced pin tract irritation symptoms after K-wire fixation, which improved after dressing changes; one patient had poor plate adherence causing skin irritation and recovered after early removal of the internal fixation. No complications such as fracture or loosening of the internal fixation devices occurred. At the final follow-up, the carrying angle of the affected elbow joint was (13.48 ± 4.19) °, the anteversion was (44.08 ± 3.80) °, the flexion was (143.27 ± 1.51) °, and the extension was (-7.23 ± 1.63) °. These values were significantly improved compared to those before surgery and showed no significant difference compared to the unaffected side. According to the Mayo Elbow Performance Score, 24 patients were rated as excellent and 2 as good. Conclusion Using computer-based mirroring technology for osteotomy simulation enables precise bone resection, which not only shortens the surgical duration but also makes the surgical procedure easier to operate, with satisfactory clinical treatment outcomes in the short-term.